PENGARUH WORKING CAPITAL TURNOVER DAN DEBT TO ASSET RATIO TERHADAP NET PROFIT MARGIN PT SEMEN INDONESIA (PERSERO) TBK PERIODE 2013-2023 - Ivan Bachtiar; Yeti Kusmawati (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of Working Capital Turnover and Debt to Asset Ratio on Net Profit Margin partially and simultaneously at PT Semen Indonesia ( Persero ) Tbk for the period 2013-2023. This research method is descriptive quantitative. The data source of this research is secondary data. The data analysis methods used are classical assumption tests, multiple linear regression equations, t tests and F tests. The results of the study based on the Working Capital Turnover t test partially had a negative and insignificant effect on Net Profit Margin, where the t test (- 1.254) < t table (2.262) with a significance level (0.241> 0.05), meaning Ho accepted Ha rejected. The Debt to Asset Ratio t test partially has a negative and significant effect on Net Profit Margin, where the t test count (-4,238) < t table (2,262) with a significance level of (0.002 < 0.05), meaning Ho is accepted Ha is rejected. The F test is influential and significant where the Fcount test (8.587)> Ftable (4.46) with a significance level (0.010 <0.05) means that Ho is rejected Ha is accepted, and the multiple linear regression equation shows Y = 33.829 - 0.002X1 + -0.558X2, meaning that if WCT and DAR = 0, then Net Profit Margin is 33, 829, while the results of the coefficient of determination R2 (R Square) = 0.682, meaning that there is a contribution of the influence of Working Capital Turnover and Debt to Asset Ratio on Net Profit Margin of 68.2% and the remaining 31.8% which is influenced by other factors not examined.